Energy and distribution in subterranean rodents: sympatry between two species of genus Ctenomys - Luna, Facundo (2007)
The low basal metabolic rate (BMR) observed in subterranean rodents, compared to that of surface-dwelling species of comparable size, has been proposed to be an adaptation to underground life. Two main hypotheses have been proposed to explain this finding, the cost of burrowing and the thermal stress. The former states that the low BMR is due to the high cost of extending the tunnel system whereas the other relates it to the possibility of overheating in burrows where evaporative and convective heat exchange are restricted. Additionally, both hypotheses related the energetics of subterranean rodent with spatial distribution. The genus Ctenomys is an excellent model to evaluate the cost of burrowing or thermal stress, since they are widely distributed, with members differing markedly in body mass. The aim of this study was to assess digging and basal energetics in two Ctenomys species that live in sympatry in a coastal grassland, but differ in their microspatial distribution by soil preference. We used the obtained energetic data to test both energy–distribution hypotheses. We measured BMR and digging metabolic rate (DMR) through open flow respirometry in two species exposed to soft and hard soils. In brief, DMR in Ctenomys talarum (100–170 g), as in Ctenomys australis (250–600 g), was unaffected by soil hardness. Within thermoneutral zone of each species, DMR/RMR quotient was lower in the smaller species. Our data did not support the thermal stress hypothesis, but the cost of burrowing hypothesis was not rejected. Other alternative hypotheses are proposed to explain the distribution of C. talarum and C. australis.